Real Time Monitering of Soil Nutrients - Mallikarjun B Halli.,1, Anil Kumar V, Basavaraju UK, Yadhunandan TN, Rajesh J (International Journal of Advanced Science and Technology, 2020)
Accidents in cities have become a major issue in today’s life and one of the main reason for this is due to the traffic congestion. Due to the congestion in traffic, it becomes more difficult for an ambulance to reach the hospital on time. The solution for this problem is the introduction of a convenient method for the smooth flow of ambulance and the method used to solve this problem is Automatic Ambulance Rescue System(AARS). This work is to implement an Intelligent Transportation System through which we can control the traffic signals which come across the ambulance automatically. This work is automated and its detects the accident spot whenever the accident occurs and sends the location details to the nearest hospital so that an ambulance can be assigned quickly by controlling the traffic lights, helping to reach the hospital on time. ESP 32 micro controller is used to control the process going on in our work. RFID tags are used to monitor and control the traffic lights.